NOVASI PENGERITINGAN ZIG-ZAG PADA RAMBUT: STUDI KASUS DI SALON VINA JENGES - Amanda Amelia; Aqilah Mudrikah; Permata Lova; Natasya Aqifa Satriya; Asrah Rezki Fauzani; Mutia Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the innovation of the zig-zag hair curling technique and its application in beauty service practices at Salon Vina Jenges. The background of this research is based on the increasingly dynamic trends in hairstyling and the growing consumer demand for unique, modern hairstyles that can enhance self-confidence. The research method used is a qualitative approach with a case study design. Data were collected through direct observation, in-depth interviews with the salon owner, hairstylists, and customers, as well as documentation as supporting data. Data analysis was conducted descriptively through the stages of data reduction, data presentation, and conclusion drawing. The results show that the zig-zag hair curling technique produces different outcomes compared to conventional techniques, creating more voluminous, dynamic textures with unique patterns. The success of this technique is influenced by the hairstylist’s skills, the use of crimper tools, and the application of heat-protectant products to maintain hair health. In addition, the level of customer satisfaction with this service is relatively high, especially in terms of final results and service quality. However, several challenges were identified, such as the durability of the style on certain hair types and the need for specialized skills in its application. Overall, the zig-zag hair curling innovation at Salon Vina Jenges can be categorized as a service development that enhances the salon’s attractiveness and competitiveness. This study is expected to serve as a reference for practitioners and academics in developing innovative and sustainable hairstyling techniques.